Visualizing ideas-heard of C-map - Neethiselvan, Rajarajeswari; Anbalagan, Suguna; Anbalagan, Surekha; Narayanan, Seetharaman (International Journal Of Community Medicine And Public Health, 2019)
Communication and interaction between teachers and students always plays a vital role in building a sound educational system where learning becomes an experience. Further enhancement of this learning and understanding of the subject can be supported and secured by a process of conceptual mapping. Conceptual mapping is a step-wise process which includes text filling, relational predicates (understanding) and finally constructing the map. It is a technical tool which is easily accessible and economical in its time use. The idea of using the concept map is still in the primitive level and more emphasis has to be made in this area to use it to its full potential in the academic field.